The Development of Evidence Law in Civil Cases Towards the Unification of Civil Procedural Law - Deny Haspada; Efa Laela Fakhriah (Yuridika, 2019)
The proof is the most important stage in settlement of a case in court because it aims to prove that a particular legal event or relationship has been made as a basis for a lawsuit. Through the burden of the proof stage, the judge will get the bases to decide between settling a case. Nevertheless, the burden of proof regulation remains plural. There are even some regulations which regulate not only the material law but also the formal law. Such a situation affects the achievement of order and legal certainty in law enforcement efforts. As is known, the nature of the procedural law is formal law, namely the law concerning the rules of the game in settlement of disputes through the court, and is binding on all parties and cannot be deviated. That is why procedural law has a public nature. For the certainty of law, therefore, the procedural law must be in the codification form of unification nature so that it can generally apply to and binding on all parties. Therefore, it is necessary to reform the civil procedural law that is codified and nationally applicable.